Vector-stimuli-responsive magnetorheological fibrous materials - Junhong Pu; Haiqiong Li; Jin Liu; Ke Li; Xiaoming Tao (Nature, 2025)
Abstract Fibrous materials that provide reversible actuation 1,2 or adapt mechanical properties 3,4 in response to external stimuli hold great promise for smart textiles 5 , soft robotics 6 and wearable technologies 7 . Although considerable progress has been made in creating fibrous materials responsive to scalar stimuli such as voltage 8 , temperature 6 , humidity 2 and ion concentration 9 , these technologies often lack directional controllability and functional diversity 10–14 . Here we report a class of vector-stimuli-responsive magnetorheological fibrous materials, guided by our engineering model integrating the structural mechanics of textiles with the magnetics of soft magnetic materials. We mass-produced soft magnetic polymer composite fibres with optimized mechanical and magnetic properties, which we then assembled into concentric helical yarns. These yarns exhibited pronounced bending and stiffening properties controlled by the direction and magnitude of magnetic fields, allowing for customized fabrics with various actuation and stiffening functionalities. We demonstrated innovative smart textiles derived from those fabrics, including an active ventilation fabric for personal moisture management, an integrated conformable gripper for handling objects of varying shapes and stiffness, and a compact remote-controllable haptic finger glove that replicates the sensation of fabric hardness and smoothness. Our work provides insights into stimuli-responsive fibrous materials, elevating them from scalar to sophisticated vector control, heralding an era of smart textile innovation.